Design, Control and Evaluation of a Prototype Three Phase Inverter in a BLDC Drive System for an Ultra-Light Electric Vehicle - Larsson, Philip; Rasmussen, Niclas (My University, 2013)
With an evolving vehicle industry there has been an increase in the demand for light electric vehicles. This thesis was conducted in order to gain further knowledge within the field of sensorless BLDC motor control for light electric vehicles. A three phase inverter was modeled and simulated in Simulink with sen- sorless BLDC motor control. A requirement specification for a three phase inverter in a drive system for a light electric vehicle was made. From the requirement specification a three phase inverter with two different sensor- less control approaches was designed in Altium Designer. The PCB was manufactured and software control algorithms as well as drivers were imple- mented. The three phase inverter and its control algorithms were tested and eval- uated. The three phase inverter operates successfully with sensorless control at a motor speed above 300RPM and fits into a light electric vehicle.
Keywords: Elkraftteknik; Electric power engineering